Event Horizon - Neill, Sam.; Fishburne, Larry; Quinlan, Kathleen (Hollywood, Calif : Paramount Pictures, 1997)
The year is 2047. Years earlier the pioneering research vessel Event Horizon vanished without a trace. A signal has been detected and the U.S. sends a ship to salvage the state-of-the-art spacecraft. What they find is interstellar terror.
Directed by Paul Anderson.
Sam Neill, Laurence Fishburne, Kathleen Quinlan, Joely Richardson.
VHS.
Closed captioned for the hearing impaired.
Keywords: Science fiction films; Horror films; Feature films; Video recordings for the hearing impaired